The minimizer for the second order diﬀerential problem with one nonlocal condition - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2017)
In this paper, we investigate the minimizer of the residual for the second order diﬀerential problem with one initial and other nonlocal Bitsadze–Samarskii condition. We obtain the representation of the minimizer and present an example.
Keywords: nonlocal conditions; least squares; Moore–Penrose inverse; minimizer